Motivation Profiles Towards Academic Reading, Substance-Related and Problematic Behaviors in Future Teachers - María de la Rocha Díaz; Inmaculada Méndez; Nuria Antón-Ros; Cecilia Ruiz-Esteban (European Journal of Investigation in Health, Psychology and Education, 2026)
Background: Motivation for academic reading is a relevant component of initial teacher training. However, little is known about whether distinct motivational profiles exist in association with patterns of substance use and problematic behaviors among prospective teachers. Methods: A cross-sectional study was conducted with 289 students (77.5% female; aged 18–34) enrolled in Early Childhood Education and Primary Education degree programs. Motivation for academic reading was assessed using the Academic Reading Motivation Scale (EMLA), while substance- and behavior-related problems were evaluated using the MULTICAGE CAD-4 questionnaire. Latent profile analysis was used to identify academic reading motivation profiles, and multivariate and post hoc analyses were performed to examine differences in scores across profiles. Results: Three motivational profiles were identified, characterized by high, intermediate, and low levels of academic reading motivation. Significant differences between profiles were observed regarding problems related to alcohol, drug use, gambling, video games, and compulsive spending. Conclusions: Academic reading motivation profiles were associated with various screening indicators for substance use and problematic behaviors. Given the cross-sectional and self-report nature of the study, these findings should not be interpreted in terms of causality. The results highlight the potential value of jointly considering academic motivation and health-related behavioral indicators in future teacher training.